2022
DOI: 10.3390/toxics10060309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Toxicity and Sublethal Effects of Acetamiprid and Dinotefuran on the Predator Chrysopa pallens (Rambur) (Neuroptera: Chrysopidae)

Abstract: Neonicotinoid insecticides affect the physiology or behavior of insects, posing risks to non-target organisms. In this study, the effects of sublethal doses of two neonicotinoid insecticides, acetamiprid and dinotefuran, against Chrysopa pallens (Rambur) (Neuroptera: Chrysopidae) were determined and compared. The results showed that acetamiprid and dinotefuran at LD10 (8.18 ng a.i. per insect and 9.36 ng a.i. per insect, respectively) and LD30 (16.84 ng a.i. per insect and 15.01 ng a.i. per insect, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…Investigation on sublethal effects of insecticides might be associated with variations in life history characteristics as growth developmental stages, fecundity, fertility (Stark & Banks, 2003;Saber et al, 2013;Rehan & Freed, 2015;Su et al, 2022), in addition to behavioral and physiological disturbances (Desneux et al, 2007). In this study, bioassay results showed that lufenuron is effective against X. luteola and LC 50 was determined as 36.6 mg l -1 .…”
Section: Discussionmentioning
confidence: 58%
“…Investigation on sublethal effects of insecticides might be associated with variations in life history characteristics as growth developmental stages, fecundity, fertility (Stark & Banks, 2003;Saber et al, 2013;Rehan & Freed, 2015;Su et al, 2022), in addition to behavioral and physiological disturbances (Desneux et al, 2007). In this study, bioassay results showed that lufenuron is effective against X. luteola and LC 50 was determined as 36.6 mg l -1 .…”
Section: Discussionmentioning
confidence: 58%
“…Using thiamethoxam in storage to prevent insect attack as an alternative to standard insecticides such as organophosphorus chemicals and pyrethroids. Recently, Su et al (2022) demonstrated that acetamiprid and dinotefuran were toxic to Chrysopa pallens and had negative effects on its growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Their toxic effects, particularly on honey bees and mammals, resulted in their gradual withdrawal from the market. Oxidative stress is one of the important cellular conditions that effects the male reproductive system, particularly spermatozoa [ 3 , 4 ]. It has been reported in different studies that neonicotinoids have negative effects on the male reproductive system, such as abnormal sperm morphology, sperm count decrease, and motility problems via different cellular pathways [ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%